Journeying to the Wonderland by African Migrants: Socioeconomic Deprivation as Drivers - Ojo, Ayodeji O; Oluwatayo, Isaac B (Journal of Ecohumanism, 2025)
Migration has been a part of human activities from time immemorial. This has increased with globalization. Despite the abundant human and natural resources in Africa, the continent is characterized by widespread poverty, inequality and a general dearth of economic opportunities. Therefore, productive resources flow from places where they are abundant to others where opportunities abound. This paper therefore examined the dynamics of migration with respect to survival and economic opportunities in Africa. The issue of migration is a mix of good and bad outcomes. The paper identified remittances, human capital development and trade as the positive aspects of migration in Africa. However, xenophobia and brain drain among others are the attendant problems of migration. Sometimes migrants are at the receiving end of ill-feelings in times of economic recessions as they are accused of taking up the already insufficient jobs from the citizens of such countries. In extreme cases, migrants are labelled as international carriers of diseases and crime perpetrators as is the case in some countries. Therefore, migration is a phenomenon with economic, health and educational dimensions. The paper recommends investments in human capital development and creation of economic opportunities through the promotion of enabling business environment in the continent.